Crowd-Driven Competitive Intelligence: Understanding the Relationship between Local Market Competition and Online Rating Distributions - Gutt, Dominik; Herrmann, Philipp; Rahman, Mohammad (Information Systems Research)

Can Experience be Trusted? Investigating the Effect of Experience on Decision Biases in Crowdworking Platforms - Görzen, Thomas (Proceedings of the 52nd Hawaii International Conference on System Sciences (HICSS))

Heart over Heels? An Empirical Analysis of the Relationship between Emotions and Review Helpfulness for Experience and Credence Goods - Müller, Michelle; Gutt, Dominik (Wirtschaftsinformatik Proceedings 2019)

A Semi-Automated Approach for Generating Online Review Templates, - Poniatowski, Martin; Neumann, Jürgen; Görzen, Thomas; Kundisch, Dennis (Wirtschaftsinformatik Proceedings 2019)

Teaching business model innovation to large and interdisciplinary IS/IT classes: A didactic approach involving peer feedback via self-recorded video presentations - Szopinski, Daniel; John, Thomas; Kundisch, Dennis (TREO Talks in conjunction with the 40th International Conference on Information Systems (ICIS))

Activate software-based business model development tools: An exploratory study - Szopinski, Daniel

Digital Tools for Teaching Business Model Innovation in Information Systems: A newly developed didactic approach comprising video-based peer feedback - Szopinski, Daniel; John, Thomas; Kundisch, Dennis

Essays on Crowd Based Idea Evaluation - Empirical Evidence from an Anonymous Online Crowd - Görzen, Thomas

Essays on Drivers and Economic Outcomes of Online-Reviews - Gutt, Dominik

All Things Considered? – Technology Design Decision-making Characteristics in Digital Startups - Bohn, Nicolai; Kundisch, Dennis (Proceedings of the 40th International Conference on Information Systems (ICIS))

Head over Feels? Differences in Online Rating Behavior for Utilitarian and Hedonic Service Aspects - Seutter, Janina; Neumann, Jürgen (Proceedings of the 40th International Conference on Information Systems (ICIS))

The App Updating Conundrum: Implications of Platform’s Rating Resetting on Developers’ Behavior - Gutt, Dominik; Neumann, Jürgen; Jabr, W.; Kundisch, Dennis (Proceedings of the 40th International Conference on Information Systems (ICIS))

Business model idea generation: An exploratory study on changing perspectives - Szopinski, Daniel; Kundisch, Dennis (2nd Business Model Conference)

How to teach business model innovation to 300+ students: An experience report - Szopinski, Daniel (2nd Business Model Conference)

The Role of Technology Pivots in Software Startups: Antecedents and Consequences - Bohn, Nicolai; Kundisch, Dennis (Proceedings of the 25th European Conference on Information Systems (ECIS))

Als Wirtschaftsinformatiker die digitale Transformation in Organisationen gestalten - Kundisch, Dennis; Beverungen, Daniel

What Drives Paid Search Success: A Systematic Literature Review - Schlangenotto, Darius; Kundisch, Dennis; Poniatowski, Martin (Proceedings of the 24th Americas Conference on Information Systems (AMCIS))

In the Eye of the Beholder? – Empirically Decomposing Different Economic Implications of the Online Rating Variance - Gutt, Dominik (Proceedings of the 25th European Conference on Information Systems (ECIS))

Is Paid Search Overrated? When Bricks-and-Mortar-Only Retailers Should Not Use Paid Search - Schlangenotto, Darius; Kundisch, Dennis; Wünderlich, Nancy (Electronic Markets)

The Traveling Reviewer Problem - Exploring the Relationship Between Offline Locations and Online Rating Behavior - Neumann, Jürgen; Gutt, Dominik; Kundisch, Dennis (Conference Abstracts of the Symposium on Statistical Challenges in Electronic Commerce Research (SCECR))

Can Companies Freeride on Public Interest Events? The Effect of Peak Days on Paid Search Advertising during the UEFA Euro 2016 - Piasecki, David; Schlangenotto, Darius (Multikonferenz Wirtschaftsinformatik 2018 (MKWI))

Much more than "same solution using a different technology" - Bohn, Nicolai; Kundisch, Dennis (Tagungsband Multikonferenz Wirtschaftsinformatik 2018 (MKWI))

Trust the Experienced? Investigating the Effect of Experience on Decision Making in the Crowd - Görzen, Thomas (Tagungsband Multikonferenz Wirtschaftsinformatik 2018 (MKWI))

Extracting the Wisdom from the Crowd: A Comparison of Approaches to Aggregating Collective Intelligence - Görzen, Thomas; Laux, Florian (Tagungsband Multikonferenz Wirtschaftsinformatik 2018 (MKWI))

With or Without You? The Influence of Search Partners on Consumer Behavior in Paid Search - Schlangenotto, Darius (Tagungsband Multikonferenz Wirtschaftsinformatik 2018 (MKWI))

Design Options of Store-Oriented Software Ecosystems: An Investigation of Business Decisions - Jazayeri, Bahar; Zimmermann, Olaf; Engels, Gregor; Küster, Jochen; Kundisch, Dennis; Szopinski, Daniel (Proceeding of International Symposium on Business Modeling and Software Design)
Nowadays companies like Apple create ecosystems of third- party providers and users around their software platforms. Often online stores like Apple App Store are created to directly market third-party solutions. We call such ecosystems store-oriented software ecosystems. While the architecture of these ecosystems is mainly derived from busi- ness decisions of their owners, ecosystems with greatly different archi- tectural designs have been created. This diversity makes it challenging for future ecosystem providers to understand which architectural design is suitable to fulfill certain business decisions. In turn, opening a plat- form becomes risky while endangering intellectual property or scarifying quality of services. In this paper, we identify three main design options of store-oriented software ecosystems by classifying existing ecosystems based on similarities in their business decisions. We elaborate on the design options, discuss their main contributions, and provide exemplary ecosystems. Our work provides aspiring ecosystem providers with the reusable knowledge of existing ecosystems and helps them to take more informed architectural decisions and reduce risks in future.

Consumer Responses to Paid Search - Empirical Evidence from a Bricks-and-Mortar Retailer - Schlangenotto, Darius

The Traveling Reviewer Problem - Exploring the Relationship Between Offline Locations and Online Rating Behavior - Neumann, Jürgen; Gutt, Dominik; Kundisch, Dennis (Workshop on IS Design and Economic Behavior (ISDEB))

An Extended Perspective of Technology Pivots in Software Startups: Towards a Theoretical Model - Bohn, Nicolai; Kundisch, Dennis (Proceedings of the 39th International Conference on Information Systems (ICIS))

What Drives Paid Search Success: A Systematic Literature Review - Schlangenotto, Darius; Kundisch, Dennis; Poniatowski, Martin (Proceedings of the 24th Americas Conference on Information Systems (AMCIS))

An Extended Perspective of Technology Pivots in Software Startups: Towards a Theoretical Model - Bohn, Nicolai; Kundisch, Dennis (Proceedings of the 39th International Conference on Information Systems (ICIS))

The Economics of Online Reviews in Markets with Variety-Seeking Consumers - Neumann, Jürgen (INFORMS Conference on Information Systems and Technology (CIST))

Towards software-based tools for business model development: Using external stimuli for business model idea generation - Szopinski, Daniel (Bosch Business Model Innovation Summit 2018)

Patterns of Store-oriented Software Ecosystems: Detection, Classification, and Analysis of Design Options - Jazayeri, Bahar; Zimmermann, Olaf; Küster, Jochen; Engels, Gregor; Kundisch, Dennis; Szopinski, Daniel (The Latin American Conference on Pattern Languages of Programs (SLPLoP))
Software companies nowadays create ecosystems of users and third-party providers around their platforms. They often provide online stores so that the third-party developments can be exposed to users directly. The resulting ecosystems differ significantly from each other in their architectural designs because their providers differ in terms of business goals and contexts. Until now, this architectural diversity and rationale behind it are not well-understood. Therefore, it is not clear which software features contribute to ecosystem’s success with respect to certain business goals and context. This hinders systematic creation of ecosystems in the future. Thus, decision-making becomes too risky; for future ecosystem providers, which may lead to creation of inefficient ecosystems that lack critical features, and for third-party providers to rely on ad-hoc choices while deciding on suitability of an ecosystem for their future career. In this paper, we introduce three design patterns for store- oriented software ecosystems by classifying the design decisions, business goals, and context of 111 store-oriented software ecosystems. Each design pattern provides an architectural solution to achieve a different business goal while supporting a different context. We discuss how the design patterns are applied together in order to achieve more business goals. Our work supports ecosystem and third-party providers by sharing practice-proven architectural solutions, helping them to take informed architectural decisions and reduce technical risks.

Towards explaining the popularity of the Business Model Canvas: A dual coding approach - John, Thomas; Szopinski, Daniel (Proceedings of the Multikonferenz Wirtschaftsinformatik 2018 (MKWI), Lüneburg, Germany)

Platform Launch Strategies - Stummer, Christian; Kundisch, Dennis; Decker, Reinhold (Business & Information Systems Engineering)

When Local Praise Becomes Cheap Talk - Analyzing the Relationship between Reviewer Location and Usefulness of Online Reviews - Neumann, Jürgen; Gutt, Dominik; Kundisch, Dennis; van Straaten, Dirk (Proceedings of the Multikonferenz Wirtschaftsinformatik 2018 (MKWI), Lüneburg, Germany)
With a growing number of online reviews, it becomes increasingly important for customers and online review platforms to find groups of reviewers who write useful reviews. Customers who review local offline businesses such as restaurants can identify themselves as locals or travelers and thus implicitly assign themselves to a specific reviewer group. This study investigates the relationship between identifying as a local and the perceived usefulness of their online reviews. Using data from Yelp.com, we empirically test hypotheses derived from attribution theory. Our results suggest that neutral and negative reviews by locals tend to be perceived as more useful than reviews by travelers. Positive reviews by locals, however, are not perceived as more useful. These findings provide significant practical implications for online review platforms and local offline businesses.

Sorting Out the Lemons - Identifying Product Failures in Online Reviews and their Relationship with Sales - Gutt, Dominik (Proceedings of the Multikonferenz Wirtschaftsinformatik 2018 (MKWI), Lüneburg, Germany)
It is well-established that both average online ratings and the number of ratings positively impact product sales. Yet, the economic implications of the information contained in the online review texts is not that well understood. In this study, we contribute to the understanding of online review texts and its economic implications by conducting and validating an unsupervised machine learning algorithm, the latent dirichlet allocation, to identify online reviews that mention product failures. Furthermore, we show that the textual information on product failures are associated with lower product sales. Our results help online review system designers, e.g., amazon, to identify these reviews and to make them easily accessible to potential customers to support the customer’s purchasing decision. Academics can build on our results by applying our validated topic identification strategy and by linking reviews mentioning product failure to a range of different outcomes.

Decomposing the Variance of Consumer Ratings and the Impact on Price and Demand - Zimmermann , Steffen; Herrmann, Philipp; Kundisch, Dennis; Nault, Barry (Information Systems Research)
Consumer ratings play a decisive role in purchases by online shoppers. Although the effect of the average and the number of consumer ratings on future product pricing and demand have been studied with some conclusive results, the effects of the variance of these ratings are less well understood. We develop a model which considers durable goods that are characterized by three types of attributes: search attributes, experience attributes, and transformed attributes the latter are conventional experience attributes that are transformed by consumer ratings into attributes that can be searched. Using informed search attributes to refer to the combination of search attributes and transformed attributes, we consider two sources of variance of consumer ratings: taste differences about informed search attributes and quality differences in the form of product failure representing experience attributes. We find that (i) optimal price increases and demand decreases in variance caused by informed search attributes, (ii) optimal price and demand decrease in variance caused by experience attributes, and (iii) by holding the average rating as well as the total variance constant, for products with low total variance price and demand increase in the relative share of variance caused by informed search attributes. Counter to intuition, we demonstrate that risk averse consumers may prefer a higher priced product with a higher variance in ratings when deciding between two similar products with the same average rating. Finally, our model provides a theoretical explanation for the empirically observed j-shaped distribution of consumer ratings in e-commerce that differs from established explanations.

Beschreib mir deine Wohnung und ich sag dir wer du bist - Eine explorative Analyse von Gastgeberpersönlichkeiten auf Airbnb - Müller, Michelle; Gutt, Dominik; Neumann, Jürgen (Multikonferenz Wirtschaftsinformatik (MKWI) 2018)

An Extended Perspective of Technology Pivots in Software Startups: Towards a Theoretical Model - Bohn, Nicolai; Kundisch, Dennis

Developing and Using an Audience Response System - Kundisch, Dennis

Decomposing the Variance of Consumer Ratings and the Impact on Price and Demand - Zimmermann, Steffen; Herrmann, Philipp; Kundisch, Dennis; Nault, Barrie (Information Systems Research)

Does the Framing of Progress Towards Virtual Rewards Matter? Empirical Evidence from an Online Community - Kundisch, Dennis; von Rechenberg, Tobias (Business & Information Systems Engineering)

Is it Worth the Effort? - A Decision Model to Evaluate Resource Interactions in IS Project Portfolios - Meier, Christian; Kundisch, Dennis; Willeke, Jochen (Business & Information Systems Engineering)

Webbasierte Classroom Response Systeme in der Hochschullehre - Eine designbasierte Fallstudie zur Unterstützung von Lehr-/Lernprozessen aus Studierendensicht - Zoyke, A.; Beutner, Marc; Herrmann, Philipp; Kundisch, Dennis; Magenheim, Johannes; Neugebauer, J. (Das Hochschulwesen)

When in Doubt Follow the Crowd: How Idea Quality Moderates the Effect of an Anchor on Idea Evaluation - Görzen, Thomas; Kundisch, Dennis (Proceedings of the 38th International Conference on Information Systems (ICIS))

"What is it Good for - Absolutely Nothing?" Exploring the Influence of Task Meaning on Creativity in Crowdsourcing - Görzen, Thomas (Proceedings of the 38th International Conference on Information Systems (ICIS))

Bitte stimmen Sie jetzt ab! - Ein Erfahrungsbericht über das Audience Response System PINGO - Kundisch, Dennis; Neumann, Jürgen; Schlangenotto, Darius (Proceedings der 15. e-Learning Fachtagung Informatik (DELFI 2017))

Study? Now! - Evaluation einer gamifizierten App zur Überwindung von akademischer Prokrastination - Klingsieck, K.; Bomm, A.; Djawadi, Behnud; Fahr, Rene; Feldotto, M.; John, Thomas; Kundisch, Dennis; Skopalik, A. (Tagung der Fachgruppen Entwicklungspsychologie und Pädagogische Psychologie (PAEPSY))